Annexin A1 Mimetic Peptide Ac2-26 Modulates the Function of Murine Colonic and Human Mast Cells - Oliveira, Marcia Pereira; Prates, Janesly; Gimenes, Alexandre Dantas; Correa, Silvia Graciela; Oliani, Sonia Maria (Frontiers in Immunology, 2021)
Mast cells (MCs) are main effector cells in allergic inflammation and after activation, they release stored (histamine, heparin, proteases) and newly synthesized (lipid mediators and cytokines) substances. In the gastrointestinal tract the largest MC population is located in the lamina propria and submucosa whereas several signals such as the cytokine IL-4, seem to increase the granule content and to stimulate a remarkable expansion of intestinal MCs. The broad range of MC-derived bioactive molecules may explain their involvement in many different allergic disorders of the gastrointestinal tract. Annexin A1 (AnxA1) is a 37 KDa glucocorticoid induced monomeric protein selectively distributed in certain tissues. Its activity can be reproduced by mimetic peptides of the N-terminal portion, such as Ac2-26, that share the same receptor FPR-L1. Although previous reports demonstrated that AnxA1 inhibits MC degranulation in murine models, the effects of exogenous AnxA1 on intestinal MCs or the biological functions of the AnxA1/FPR2 system in human MCs have been poorly studied. To determine the function of MCs toward the possibility of AnxA1-based therapeutics, we examined in WT and IL-4 knockout mice under peptide Ac2-26 treatment, the role of spontaneous and compound 48/80 stimulated colonic MC degranulation and cytokine production. In vitro, using human mast cell line HMC-1, we demonstrated that exogenous AnxA1 peptide is capable of interfering with the HMC-1 degranulation in a direct pathway through formyl peptide receptors (FPRs). We envisage that our results can be used as a therapeutic strategy to reduce the release of MC mediators in inflammatory allergic processes.